Bernstein's Puzzle: Peasants, Accumulation and Class Alliances in Africa. (July 2016) - O'laughlin, Bridget
Abstract : To establish the significance of Henry Bernstein's theoretical work on the dynamics of agrarian class struggles in Africa, this paper discusses two important political debates in which he has been both observer and participant, and that have oriented much of the subsequent Marxist work done in Africa on agrarian change. The first was the heated discussion begun over 40 years ago around Nyerere's 'African socialism' and the failures of the ujamaa policy of villagization. The second is the still unsettled debate around programmes of redistributive land reform in South Africa. Bernstein's distinction between the peasantry and petty commodity production allowed him to apply Lenin's theory of peasant differentiation to new contexts, and to locate African class struggles within the contradictions between capital and labour. He thus disposed of two competing visions: the harmonic peasant community and the maximizing entrepreneurial peasant hindered by the absence of markets. Yet, this paper argues, his focus on class formation within the peasantry can also limit our understanding of class alliances in the politics of anti‐capitalist struggles in Africa.